Comparison of functional outcome of cemented total hip replacement versus cemented dual-mobility cup total hip replacement for the management of displaced femoral neck fractures in the active elderly patients. Issue 5 (September 2021) - Rashed, Ramy A M; Sevenoaks, Hannah; Choudry, Qaisar A; Kasem, Mohammed S; Elkhadrawe, Tarek A; Eldakhakhny, Magdy M
Introduction: Current guidelines recommend treating displaced femoral neck fractures with a total hip replacement in fit and active elderly patients. Dislocation remains the main complication. Dual-mobility cup (DMC) hip replacements maybe a solution to decrease dislocation, with the benefit of increasing stability, achieving better range of motion and functional outcomes. Patients and methods: This is a prospective randomised controlled trial which included 62 patients with Garden III and IV femoral neck fractures. The mean age was 67.2 years. 30 males and 32 females were included, randomised and allocated to 2 treatment groups; a cemented DMC replacement group, or a cemented 32-mm head total hip replacement (THR). The posterior approach was used in all patients. Postoperative functional outcome was assessed using Harris Hip Score (HHS). Health-related quality of life (HRQoL) was assessed using the SF-36 questionnaire. Results: The mean HHS for the DMC group at 4, 6 and 12 months were higher than mean HHS scores for the THR group ( p < 0.001). The range of motion at 1 year was statistically better in the DMC group compared to the THR group ( p < 0.001). The DMC showed a statistically better effect on the HRQoL measurements as compared to the THR group. There were no dislocations in both groups. Conclusions: DMC hip replacements provide better functional, patient reported outcomes, and range of motion than the conventional THR. Combined with its stability, DMC replacements are a useful solution in managing femoral neck fractures in active elderly patients. Trial serial number 020841 (IRB Number 00007555).